RANCANG BANGUN PURWARUPA SISTEM REGISTRASI MASUK PINTU TOLL UNTUK KENDARAAN MENGGUNAKAN LONG RANGE RADIO (LORA) - Nainggolan, Ferdo; Caily, Regina; Lubis, Sari; Indra ER, Ngurah; Elba Duta Nugraha, I Putu (Jurnal SPEKTRUM; Vol 11 No 3 (2024): Jurnal SPEKTRUM, 2024)
The inefficiency of toll gate systems is one of the main causes of traffic congestion on toll roads. This condition requires an innovative solution to detect and process vehicle information before the vehicle reaches the toll gate. This study aims to develop a prototype that uses ESP32, LoRa, GPS, OLED, and Internet of Things (IoT) technology to provide a solution to this problem. The developed prototype uses ESP32 as the main microcontroller, LoRa for long-distance communication, GPS to track the vehicle's location, and OLED as the information display. This system is designed for vehicles to perform real-time registration. The test results show that this prototype can function well in registering vehicle data that will enter the toll gate remotely. With the implementation of this technology, it is expected to reduce the waiting time for toll road users caused by the long queue times of vehicles at conventional toll gate registration systems .